Development and Application of a Percolation Velocity Monitoring Method in Multiphase Percolation Physical Experiments - Cuo Guan; Xianjie Li; Ke Hu; Chen Liu; Hong Du; Ruokun Xian (Geofluids)
Unlike conventional single-phase seepage monitoring methods, monitoring multiphase flow in porous media is more complex. This paper addresses this complexity by analyzing the heat transfer in porous media models under multiphase seepage conditions. It introduces a set of theories, methods, and devices to effectively monitor the flow velocity in multiphase seepage processes. Utilizing a self-developed single-point self-heating temperature-sensing device combined with saturation testing at monitoring points, we establish a method to determine the relationship between different saturation and resistivity, as well as the saturation and thermal conductivity of the reservoir model, which provides essential parameter support for the calculation of results during flow velocity monitoring. The effectiveness of the flow velocity monitoring method was confirmed through a one-dimensional constant velocity multiphase seepage experiment. Furthermore, oil-water two-phase seepage simulation experiments were conducted based on the sandpack model. By comparing the real oil-water flow velocity with the monitored velocity, the accuracy can reach over 95%, validating the accuracy and reliability of the method proposed in this paper. The seepage flow velocity monitoring theory and technology established herein offer corresponding theories and methods for obtaining fluid seepage velocity in porous media with multiphase fluids.